Registry data analysis of hematopoietic stem cell transplantation on systemic chronic active Epstein–Barr virus infection patients in Japan. Issue 6 (30th March 2022) - Yamamoto, Masahide; Sato, Maho; Onishi, Yasushi; Sasahara, Yoji; Sano, Hideki; Masuko, Masayoshi; Nakamae, Hirohisa; Matsuoka, Ken‐ichi; Ara, Takahide; Washio, Kana; Onizuka, Makoto; Watanabe, Kenichiro; et al.
Abstract: The effects of allogeneic hematopoietic stem cell transplantation (allo‐HSCT) on systemic chronic active Epstein–Barr virus infection (sCAEBV) are yet to be analyzed in a large number of patients. Using the Japanese registry database, Transplant Registry Unification Management Program, we investigated the outcomes of 102 sCAEBV patients who underwent allo‐HSCT. The median age at HSCT was 21 years, and the three‐year overall survival (3‐year OS) rate was 72.5%. Of the 90 patients whose viral load after allo‐HSCT was evaluated, 56 (62.2%) achieved a virological complete response, defined by the complete resolution of disease activity with a significant decrease in EBV‐DNA in peripheral blood. The multivariate Cox proportional hazard model indicated that advanced age, in adolescents and young adults (AYA) (age, 15–39) and adults (age, ≥40 years) was a risk factor of poor OS. The hazard ratios (HRs) of the AYA and adult groups were 10.87 (95% confidence interval [CI]: 1.98–59.56, p = .006) and 15.93 (95% CI: 2.45–103.8, p = .004), respectively. Disease activity (HR 5.74), elevated soluble IL‐2 receptor (sIL‐2R) (≥ median, 691 U/mL) at HSCT (HR 6.93), and conditioning without radiotherapy (HR 3.53) were also independently associated with poor survival. Notably, 79% of radiotherapy doses were less than 6 Gy. Regardless of the presence of hemophagocytic lymphohistiocytosis, the group with a high sIL‐2R level (≥2000 U/mL) showed a poorer prognosis. Although allo‐HSCT is the only curative therapy for sCAEBV, treatment strategies need to be improved for high‐risk patients, especially those with high levels of sIL‐2R.